Hydatidoperitoneum: (Heterotopic gallbladder) - Bortagaray, Carlos; Errandonea, Jorge; Rodríguez-Arraras, Nelson; Villar, Ariel (Cirugía del Uruguay, 1972)
The authors present two cases of hydatid peritoneum with heterotopic gall bladders, coexisting with insheating membrane. 'I'his strange type of parasitosis has not been described in the existing bibliography.